Treatment of Pulmonary Carcinoid Tumors With Bronchoscopic Cryotherapy: A 28-Year Single-center Experience. Issue 1 (January 2022) - Perikleous, Periklis; Mayer, Nora; Finch, Jonathan; Beddow, Emma; Anikin, Vladimir; Asadi, Nizar
Abstract : Background: Pulmonary carcinoids are rare tumors originating from neuroendocrine cells in the lungs. Because of their potentially infiltrative nature, surgical resection remains the treatment of choice. However, not all patients with technically resectable disease will be able to undergo surgery, primarily because of poor lung function or medical co-morbidities. Centrally located, intraluminal tumors have been reported to be amenable to bronchoscopic treatment. We specifically examined the role of cryotherapy in the treatment of bronchial carcinoid tumors. Methods: Sixty-three patients (52.38% female) who underwent a combined total of 243 cryotherapy procedures for treatment of bronchial carcinoid between 1992 and 2020 in our institution were included in the study. Following discussion in multidisciplinary meetings, patients were considered for first-line cryotherapy when lung resection was deemed not possible or when they had rejected surgery. Results: Cryotherapy resulted in complete remission in 21 (33.33%) patients with maximum tumor diameter less than 20 mm (mean: 11.08 mm, 95% confidence interval: 8.76-13.40), and allowed 22 (34.92%) patients with larger lesions (mean: 24.04 mm, 95% confidence interval: 18.78-29.30) to proceed with parenchymal sparing resections. Marked symptomatic relief ( P <0.001) was reported by 58 (92.06%) patients. The median follow-up was 33 months (range: 0 to 243 mo). One (1.59%) patient was diagnosed with recurrence in a contralateral lobe 3 years after surgery and was treated with radiofrequency ablation. Conclusions: In the absence of a definitive randomized controlled trial comparing bronchoscopic treatment with surgical resection, we provide evidence on the safety and efficacy of cryotherapy and encourage wider adoption of this inexpensive and minimally invasive technique for treatment of bronchial carcinoids.